Vegetarianism in the Anthropocene: Richard Powers and Jonathan Franzen. Issue 2 (7th February 2019) - Savvas, Theophilus
ABSTRACT: This article uses the representation of vegetarianism in Richard Powers' The Echo Maker (2006) and Jonathan Franzen's Purity (2015) as a way to think about broader issues of ecological engagement. It argues that these issues are related to the ways in which each writer approaches questions of subjectivity and form after postmodernism. It concludes that the posthumanist dimension of Powers' novel, achieved through formal experimentation, is a more successful engagement with the questions posed by the age of the Anthropocene than Franzen's continued realism.